Pengaruh Kemudahan Penggunaan, Pengalaman Sebelumnya, Kepercayaan Konsumen dan Persepsi Harga Terhadap Minat Beli Dalam Transaksi Belanja Online (Studi pada Produk Fashion di Area Semarang) - Ayuningrum, Shinta; Idris, Idris (Diponegoro Journal of Management, 2016)
The purpose of this research is to know how the influence of the ease of use, past experience, consumer trust and perception of price towards consumer purchase intention on online shopping transaction. Many online shopping sites today has creating fierce competition among online shopping sites. It was done with the aim to get consumers' attention with the hope to increase the interest of consumer to purchase on their website. That makes researchers want to find out what factors are needed to improve consumer purchase intention towards online shopping transactions, especially on purchase fashion products.The sample in this research were internet users in Semarang who already shop online to purchase fashion products. The samples were 200 people selected using purposive sampling through an online questionnaire. Analysis of the data used in this research are validity and reliability, the classic assumption test, multiple regression analysis, goodness of fit test.The results of the multiple linear regression analysis is, Y = 0,187 X1 +0,238 X2 + 0,176 X3 + 0,279 X4. The most influential independent variable towards the dependent variable is perception of price (0,279), followed by past experience (0,238), ease of use (0,187) and the last one is consumer trust (0.176). T test results showed that the ease of use, past experience, consumer trust and perception of price variables have a positive and significant influence towards purchase intention. The coefficient of determination obtained from the independent variable in this research is 52,2%, while the remaining 47,8% is influenced by other variables outside the model of this research.